PERIBAHASA MELAYU SAMBAS: SEBUAH INVENTARISASI SERTA ANALISIS JENIS DAN FUNGSI - Annisa, Siwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The research of Sambas Malay proverb based on the existence of proverb among Sambas Malay people that almost extinct. Proverb was used to control attitude before the existence of law of criminal and civil case. The proverb it self functions as advice, satire, compliment, diplomatic language. This proverb research focuses to take inventory, classifying types and functions of Sambas Malay proverb, also providing lesson plan of proverb at school in Curriculum 2013. The result research of Sambas Malay proverb take invetory 300 proverbs. The proverb are classified based on the types, they are bidalan in total 94, pepatah in total 24, perbilangan in total 7, perumpamaan in total  147, lidah pendeta in total 0, kiasan in total 12, tamsil in total 9, and ibarat in total 7. While Sambas Malay proverb which classified based on the function, they are as advice in total 77, as satire in total 155, as compliment in total 20, and diplomatic language in total 5, also as literary work or conversation in total 43. The result of Sambas Malay proverb also provides lesson plan which is able to be applied in Curriculum 2013.   Keywords: Proverb, Inventory, Type, Function, Lesson Plan